Ideological Underpinnings in President John Dramani Mahama’s 2013 State of the Nation Address: A Critical Discourse Analysis - Kojo Fenyi; Georgina Afeafa Sapaty (Linguistics Initiative, 2021)
This study sets out to investigate, examine and understand the hidden ideologies and ideological structures/devices in the 2013 State of the Nation Address of President John Dramani Mahama. The study specifically aimed to (i) ascertain the ideologies embedded in the speech and (ii) investigate linguistic expressions and devices which carry these ideological colourations in the speech under review. It uses Critical Discourse Analysis as the theoretical framework to examine the role of language in creating ideology as well as the ideological structures in the speech. These hidden ideologies are created, enacted and legitimated by the application of certain linguistic devices. The researchers deem a study of this nature important as it will expose hidden motives that Ghanaian presidents cloth in language in order to manipulate their audience through their speeches in order to win and/or sustain political power. Through thematic analysis, it was revealed that Mahama projected these ideologies in his speech: ideology of positive self-representation, ideology of human value, ideology of economic difficulty, ideology of power relations and ideology of urgency. It also revealed that Mahama projects his ideologies through the following ideological discursive structures: pronouns, biblical allusion and metaphor. The study has shown that language plays a crucial role in human existence as a means of socialisation. Language has been revealed as a means of communicating ideologies and events of the world. In the tradition of CDA, this study has confirmed that text and talk have social and cultural character and that discourse functions ideologically.